Body build, strength and endurance performance in elite sport and alpine climbers - a pilot study - Rokowski, R.; Staszkiewicz, R.; Maciejczyk, M.; Szygula, Z.; Michailov, M.; Szymura, J.; Wiecek, M.; Regwelski, T. (Journal of Kinesiology and Exercise Sciences, 2017)
Aim of the study: The aim of the study was to compare the main indicators characterizing body build, including the strength and endurance potential of elite mountain and rock climbers. Methods: The study was comprised of high-class male athletes, performing rock climbing and mountain climbing and involved anthropometric, biomechanical (maximum grip strength in two hand positions and maximum absolute muscle strength of the forearms and arms) and physiological (maximal oxygen uptake [VO2max], second ventilatory threshold [VT2] measured in laboratory conditions and physiological responses during climbing on an indoor climbing wall) measurements. Results: The absolute and relative strength was higher in rock than mountain climbers. Mountain and rock climbers were characterized by a high aerobic performance (VO2max: 64 ml/kg/min), but differed in the exercise intensity at VT2 (80.6%VO2max in mountain climbers, and 70.3%VO2max in rock climbers). The duration of the effort performed on climbing wall was shorter in the mountaineers than the sports climbers. Conclusion: The mountain climbers have a higher body mass and BMI compared to rock climbers. The mountain climbers are characterized by a lower level of upper limb muscle strength than rock climbers. The mountaineers compared to the rock climbers have better endurance performance.